Microbial Melanin: Recent Developments and Challenges in the Production, Extraction, Purification and Application of Microbial Melanin - Fatima, Meraj (Annual research & review in biology, 2023)
A class of biopolymers known by the common name melanin has several potential uses in the medicinal sciences, bioelectronics, cosmeceutical and bioremediation. These pigments wide distribution indicates that they help a variety of life forms- fight biotic and abiotic stressors. Different types of melanin, such as eumelanin, pheomelanin, allomelanin, pyomelanin, and neuromelanin, are produced by the oxidative polymerization of phenolic compounds in fungi and bacteria, primarily via the 1,8-dihydroxynaphthalene [DHN] or 3,4-dihydroxyphenylalanine [DOPA] pathways. The tyrosinase, laccase, and polyketide synthase are the groups of enzymes that are primarily responsible for the production of melanin in many microorganisms. Research has indicated that utilising recombinant technologies in conjunction with culture parameter manipulation can enhance melanin yield for industrial production. Its low solubility has hindered the development of extraction techniques despite tremendous efforts, and its heterogeneous structural complexity has hindered structural elucidation, which limits the full potential of its biotechnological applications. The process of extraction may differ slightly depending on the kind of tissue and where the melanin is located. Melanin pigments from various taxa of life (like Sepia, bacteria, fungi) have been the subject of countless investigations to expand our understanding of them and enable their effective use in a wide range of applications. Due to these studies, there is an immediate need for a thorough review of melanin pigments that have been isolated from microorganisms. A review that covers biosynthesis, bioproduction, characterization, and possible applications will aid researchers from a variety of backgrounds in appreciating the significance of microbial melanins and in organizing their own melanin-related research projects. In order to achieve this, the current study contrasts traditional and cutting-edge concepts for environmentally sustainable melanin extraction processes.